Study of solvent system for biodiesel production from Sludge Palm Oil (SPO) by enzymatic transesterification - Nasaruddin, Ricca Rahman; Alam, Md. Zahangir; Jami, Mohammed Saedi (2012)
Biodiesel is a non-toxic renewable fuel that has been highly demanded because it reduces the emission of air pollutants, thus a good alternative for the petroleum-derived fuel which is now having depletion, unstable price escalation and causes environmental problems. In this study, sludge palm oil (SPO) which is a low cost and abundantly produced waste oil was investigated to produce biodiesel by direct enzymatic transesterification using lipase. The lipase was produced locally by Candida cylindracea from a low cost basal medium, palm oil mill effluent (POME) in order to eliminate the higher cost of commercial lipases. Several factors in solvent system were studied to enhance the biodiesel production. Ethanol was selected as the acyl acceptor because it gave higherpercentage of yield and conversion of free fatty acids (FFAs) into biodiesel than the methanol. The optimum ethanol-to-SPO molar ratio was found to be 4:1 while the increasing of water content reduced the activity of the lipase thus it gave lower percentage of yield and conversion of FFAs into biodiesel.Thus, enzyme loading investigation was done to limit the use of water. It was found that enzyme loading at 10U with water content of 7% volume of water per volume of SPO (v/v SPO) gave higher percentage of yield and conversion of FFAs into biodiesel. It was also found that the addition of tert-butanol with 1:1 tert-butanol-to-SPO molar ratio increased the percentage of the yield and conversion of FFAs into biodiesel by 80.54% and 25.68% respectively.